Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

Multi–scale drift characteristics of Ulva prolifera in the Yellow Sea derived from deep learning–based MODIS and Sentinel-1 observations - Xiaomeng Geng; Huiru Li; Ruolan Fan; Yunlong Zhao; Enran Guo; Runbing Qi (Marine Pollution Bulletin, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Characterization and encapsulation properties of pectic polysaccharides derived from Choerospondias axillaris fruit - Hao Liu; Ruolan Du; Hongxiang Li; Wenbo Zhao; Liang Leng; Jun Lu; Haiqiang Zhang; Sanyin Zhang (Carbohydrate Polymers, 2026)

Multi-media distribution, source apportionment, and risk assessment of legacy and current-use organophosphorus pesticides in typical agricultural watersheds of China - Chengcheng Bu; Limin Ma; Weiwei Zhang; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Qi Wang; Yuefei Ruan; Chong Chen (Water Research, 2026)

Occurrence and differential spatiotemporal distribution of pesticides in a plateau lake basin with intensive vegetable cultivation: A case study in Qilu Lake Basin - Qihui Zhao; Limin Ma; Chengcheng Bu; Yu Hua; Ruolan Jia; Chong Chen (Environmental Research, 2026)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Nanozyme-mediated drug ion-exchange strategy ameliorates inflammatory bowel disease by scavenging ROS and reprogramming proinflammatory macrophages - Hongyan Lu; Ying Cheng; Xiangling Pu; Xingtao Zhao; Ruolan Li; Ruiqi Sun; Xiaoman Xie; Mingyue Wu; Shuo Zhang; Qiong Pan; Jin Chai (Chemical Engineering Journal, 2025)

Hierarchical sulfur vacancy engineering via lattice strain for commercial-grade photocatalytic H2O2 generation in Sm3+-doped ZnIn2S4 - Ruolan Zhao; Chen Chen; Yachao Xu; Yue Qu; Peng Yu; Ying Wang (Chemical Engineering Journal, 2025)

Defect-engineered Z-scheme BiOBr/TiO2 heterojunctions with interfacial potential wells for selective CO2 photoreduction - Shijie Liu; Ruolan Zhao; Yachao Xu; Maoxiang Li; Zihan Ma; Xin Chang; Ying Wang; Mingyi Zhang (Chemical Engineering Journal, 2025)

Therapeutic potential of Angelica sinensis derivatized carbon dots in ameliorating chemotherapy-induced anemia - Ruolan Kong; Yujiao Yuan; Jiaxing Liu; Kai Cheng; Yifan Zhang; Xiwen Zhang; Peng Zou; Yan Huang; Jinyu Ma; Chenxin He; Hui Kong; Yan Zhao; et al. (Journal of Molecular Histology, 2025)

Water-saving irrigation suppresses on soil-crop pathogenicity: Insight on the co-host of virulence factors and antibiotic resistance genes - Lizhi Zhao; Yuhui Li; Qifan Yang; Ruolan Li; Houyu Li; Yan Xu (Journal of Hazardous Materials, 2025)

A reversible fluorescence probe enables bioimaging and toxicity evaluation of lithium ion in living human cells - Cheng Gong; Peiming Zhang; Ya Liu; Ruolan Chen; Kai Huang; Weizhun Yang; Lirong Gao; Ming Xu; Xuezhi Yang; Yin Liu; Qian Liu; Bing Yan; et al. (Journal of Hazardous Materials, 2025)

The effect of probiotics supplementation on cancer-treatment complications: a critical umbrella review of interventional meta-analyses - Zhao Yang; Shijie Zhang; Lu Ying; Wenjing Zhang; Xiaoyang Chen; Youfeng Liang; Ruolan Chen; Keying Yao; Chunhui Li; Changyuan Yu; Parmida Jamilian; Meysam Zarezadeh; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Preparation of ZnWO4/Bi4O5I2 composite photocatalyst and study of its antibacterial properties - Ling Zhang; Zixin Wang; Ruolan Wei; Tengyuan Gao; Jingmei Li; Luyin Zhao; Deming Han; Xiulong Li (Journal of Water Process Engineering, 2025)

Edge-Based Dynamic Spatiotemporal Data Fusion on Smart Buoys for Intelligent Surveillance of Inland Waterways - Ruolan Zhang; Chenhui Zhao; Yu Liang; Jingfeng Hu; Mingyang Pan (Journal of Marine Science and Engineering, 2025)
Increasing vessel traffic in narrow, winding inland waterways has heightened the risk of accidents, driving the need for improved surveillance and management. This study addresses the challenge of real-time processing and synchronization of voluminous video and AIS data for effective waterway management. We developed a surveillance method utilizing smart buoys equipped with sensors and edge computing devices, enabling dynamic spatiotemporal data fusion. The integration of AIS data with advanced computer vision techniques for target detection allows for real-time traffic analysis and provides detailed navigational dynamics of vessels. The method employs an enhanced Long Short-Term Memory network for precise trajectory prediction of AIS data and a single-stage target detection model for video data analysis. Experimental results demonstrate significant improvements in ship detection accuracy and tracking precision, with an average position prediction error of approximately 1.5 m, which outperforms existing methods. Additionally, a novel regional division and a Kalman filter-based method for AIS and video data fusion were proposed, effectively resolving the issues of data sparsity and coordinate transformation robustness under complex waterway conditions. This approach substantially advances the precision and efficiency of waterway monitoring systems, providing a robust theoretical and practical framework for the intelligent supervision of inland waterways.

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Injectable exosome-loaded quaternized chitosan/oxidized sodium alginate hydrogel with self-healing, bioadhesive, and antibacterial properties for treating combined radiation-wound injury - Guanqun Peng; Jia Hu; Jinnan Guo; Jiahui Dong; Yuanyuan Zhao; Tong Ye; Fengjun Xiao; Zhiyun Meng; Hui Gan; Ruolan Gu; Peng Han; Wenzhong Sun; et al. (Chemical Engineering Journal, 2024)

Ion presence during thermal processing modulates the performance of rice albumin/anthocyanin binary system - Yabin Guo; Ruolan Fang; Yiyuan Zhen; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Research International, 2024)

Response of organic aerosol in Beijing to emission reductions during the XXIV Olympic Winter Games - Qipeng Qu; Shuxiao Wang; Bin Zhao; Ruolan Hu; Chengrui Liang; Haowen Zhang; Shengyue Li; Boyang Feng; Xuan Hou; Dejia Yin; Jinhong Du; Yangxi Chu; et al. (Science of The Total Environment, 2024)

Incorporating edible oil during cooking tailors the microstructure and quality features of brown rice following heat moisture treatment - Yabin Guo; Ruolan Fang; Zhuoting Wu; Gaolei Xi; Dongling Qiao; Genfa Wang; Ting Cui; Liang Zhang; Siming Zhao; Binjia Zhang (Food Research International, 2024)

A critical review on the thermal management of data center for local hotspot elimination - Ruolan Zhao; Yahui Du; Xiaochen Yang; Zhihua Zhou; Wufan Wang; Xueqing Yang (Energy and Buildings, 2023)

Preparation and application of cinnamon-Litsea cubeba compound essential oil microcapsules for peanut kernel postharvest storage - Haoxin Lv; Shanshan Huo; Lingli Zhao; Hanxiao Zhang; Yijun Liu; Shichang Liu; Akio Tani; Ruolan Wang (Food Chemistry, 2023)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)

Identification and functional characterization of a p-coumaroyl CoA 2′-hydroxylase involved in the biosynthesis of coumarin skeleton from Peucedanum praeruptorum Dunn - Ruolan Yao; Yucheng Zhao; Tingting Liu; Chuanlong Huang; Sheng Xu; Ziwei Sui; Jun Luo; Lingyi Kong (Plant Molecular Biology, 2017)